BJP is linking its articles to the IUPHAR/BPS Guide to PHARMACOLOGY - McGrath, J C (Br J Pharmacol, 2015)
LINKED EDITORIALS: This Editorial is part of a series. To view the other Editorials in this series, visit: http://onlinelibrary.wiley.com/doi/10.1111/bph.12956/abstract; http://onlinelibrary.wiley.com/doi/10.1111/bph.12954/abstract; http://onlinelibrary.wiley.com/doi/10.1111/bph.12955/abstract and http://onlinelibrary.wiley.com/doi/10.1111/bph.12856/abstract. VIDEO: To view the video on the IUPHAR/BPS Guide to PHARMACOLOGY, visit: https://www.youtube.com/watch?v=Qhy3q33VtRI